Prevention of Early Jaundice in Babies Through Empowerment: Quasi-Experiments with Pregnant Women - Nainggolan, Lenny; Wahyuni, Tengku Sri; Rahayu, Teta Puji; Ngestiningrum, Ayesha Hendriana (Universitas Airlangga, 2025)
Background: Jaundice is a health problem for newborns that occurs in around 60% of term pregnancies and around 80% of premature pregnancies. Babies who experience severe jaundice need to receive proper examination and treatment to prevent morbidity and death. Mothers' role in overcoming the lack of breast milk in newborn babies is important. Hence, they need to be educated and empowered to avoid health problems that can be prevented if mothers and babies receive timely care. Objectives: This research aims to analyze the effect of maternal empowerment on preventing early jaundice in babies in Pematangsiantar City. Method: The method used was the quasi-experimental design with a non-equivalent control group design model, carried out on 62 pregnant women and jaundice assessment on 62 newborns (31 pregnant women who were given education and monitored for empowerment and 31 mothers who were given education but not monitored). Sampling was taken using consecutive sampling. Data collection used a validated questionnaire and statistical tests with chi-square. Results: Statistical tests showed that, after empowering mothers, 90.3% implemented IMD in the intervention group and 83.9% in the control group (p=0.707). The results showed that after empowering mothers there were 93.5% of babies did not experience jaundice, and in the control group 71.0% did not experience jaundice. Statistically, there was a difference between the two groups (p=0.46). Conclusion: Maternal empowerment can influence the prevention of jaundice in babies. Implementation of empowerment through providing education about IMD, breastfeeding, and jaundice needs to be carried out by health workers.